Design, Synthesis and Biological Evaluation of a Radiolabelled Antagonist-Bombesin Analog as Targeting Vector - Wael, Abd-Elgaliel (2008)
The gastrin releasing peptide receptor (GRP-R) is over-expressed on a number of tumors and cancer cell lines including pancreas, prostate, breast, gastrointestinal and small cell lung cancer (SCLC). Radiolabeled bombesin (BBN) analogues have exhibited high binding affinity and specificity to the GRP-R. A bombesin analogue with an antagonist targeting-vector at the C-terminus, DOTA-aminohexanoyl-[D-Phe(6), Leu-NHCH(2)CH(2)CH(3)(13), des Met(14)] BBN[6-14] (1, “Bomproamide”), has been synthesized and displays high binding affinity (IC(50) = 1.36 ± 0.09 nM) against (125)I-Tyr(4)-BBN in in vitro competitive assays using PC-3 cells. Maximum internalization of (111)In-1 reached 14% in PC-3 cells after 45 minutes of incubation. Rapid (0.25-hour PI) and high (12.21 ± 3.2 %ID/g) pancreatic uptake of (111)In-1 was observed in healthy CF-1 mice and 90% of the activity was blocked by co-injection of 100 μg of BBN. Rapid (0.25-hour PI) and high uptake (6.90 ± 1.06 %ID/g) was observed in PC-3 prostate cancer xenografts in SCID mice, as well as visualized clearly in a SPECT/CT study. These results support the use of a bombesin construct with an antagonist C-terminal vector as a candidate of choice for specific in vivo imaging of tumors over-expressing GRP-receptors.